Staining of fungal cell walls with fluorescent brighteners: flow-cytometric analysis - Hejtmánek, M; Dolezel, J; Holubová, I (Folia microbiologica, 1990)
Spore walls of Backusella lamprospora (Mucorales) were stained with ten fluorescent brighteners (FB) and the intensity of their fluorescence was determined. The fluorescence was most intense with Uvitex 2B (100%), other brighteners yielding lower fluorescence intensities: Blankophor BA 267% and BA 200% about 75%, Rylux BSU about 50%, other Rylux agents 10-30%. The agents most suitable for microscopic diagnostics of human and animal mycoses are Uvitex 2B, Blankophor BA 267% and BA 200%, Rylux BSU, and also Rylux BS and PRS. The regulation of excessive fluorescence of fungal cells during microscopic observation is discussed. For the purposes of microscopic diagnosis of human and animal mycosis Uvitex 2B, Blankophor BA 267% and BA 200%, Rylux BSU and, possibly, Rylux BS and PRS are recommended.
Keywords: Spores, Fungal; spory hub; mykózy; buněčná stěna; průtoková cytometrie; Animals; fluorescenční barviva; Humans; Mycoses; Fluorescent Dyes; lidé; Mucorales; Flow Cytometry; zvířata; Staining and Labeling; Cell Wall; barvení a značení